Niches and Seasonal Changes, Rather Than Transgenic Events, Affect the Microbial Community of Populus × euramericana ‘Neva’ - Huang, Yali; Dong, Yan; Ren, Yachao; Wang, Shijie; Li, Yongtan; Du, Kejiu; Lin, Xin; Yang, Minsheng (Frontiers in Microbiology, 2022)
Exploring the complex spatiotemporal changes and colonization mechanism of microbial communities will enable microbial communities to be better used to serve agricultural and ecological operations. In addition, evaluating the impact of transgenic plants on endogenous microbial communities is necessary for their commercial application. In this study, microbial communities of Populus × euramericana Neva carrying Cry1Ac-Cry3A-BADH genes (ECAA1 line), Populus × euramericana Neva carrying Cry1Ac-Cry3A-NTHK1 genes (ECAB1 line), and non-transgenic Populus × euramericana Neva from rhizosphere soil, roots, and phloem collected in different seasons were compared and analyzed. Our analyses indicate that the richness and diversity of bacterial communities were higher in the three Populus × euramericana Neva habitats than in those of fungi. Bacterial and fungal genetic-distance-clustering results were similar; rhizosphere soil clustered in one category, with roots and phloem in another. The diversity and evenness values of the microbial community were: rhizosphere soil > phloem > root system. The bacterial communities in the three habitats were dominated by the Proteobacteria, and fungal communities were dominated by the Ascomycota. The community composition and abundance of each part were quite different; those of Populus × euramericana Neva were similar among seasons, but community abundance fluctuated. Seasonal fluctuation in the bacterial community was greatest in rhizosphere soil, while that of the fungal community was greatest in phloem. The transgenic lines ECAA1 and ECAB1 had a bacterial and fungal community composition similar to that of the control samples, with no significant differences in community structure or diversity among the lines. The abundances of operational taxonomic units (OTUs) were low, and differed significantly among the lines. These differences did not affect the functioning of the whole specific community. Sampling time and location were the main driving factors of changes in the Populus × euramericana Neva microbial community. Transgenic events did not affect the Populus × euramericana Neva rhizosphere or endophytic microbial communities. This study provides a reference for the safety evaluation of transgenic plants and the internal colonization mechanism of microorganisms in plants.